Pengaruh Rating Risiko ESG dan Pengungkapan Keanekaragaman Hayati terhadap Kinerja Keuangan Perusahaan - Liza Fitra Utami; Nurzi Sebrina (Universitas Negeri Padang, 2024)
This study aims to examine the effect of ESG risk rating and biodiversity disclosure on firm's financial performance. This research adopts a causal associative approach with quantitative methodology. The population includes all companies listed on the Indonesia Stock Exchange in 2022. Using a purposive sampling method, 87 companies were selected as the research sample for the one-year observation period of 2022. The firm’s financial performance as dependent variable is measured by Return on Assets and Tobin's Q. ESG risk rating, as one of the independent variables, utilizes scores issued by Morningstar Sustainalytics. Biodiversity disclosure, another independent variable, is measured using GRI 304 disclosure index, where each disclosure item is scored between 0 to 3. F-test results indicate that the independent variables jointly affect the dependent variable. But, t-test results show that there are no significant effect of ESG risk rating and biodiversity disclosure on firm’s financial performance.